I am reposting a question from Math Overflow, because it seems it gets no attention.

Let $\Omega\subset \mathbb R^{d=3}$ is a bounded and Lipschitz domain. Let $u\in H_g^1(\Omega)$ satisfy the weak formulation $$a(u,v)+\int\limits_{\Omega}{f(u)vdx}=0,\,\forall v\in H_0^1(\Omega)\cap L^\infty(\Omega)\quad\quad (*)$$ where $a(u,v)=\int\limits_{\Omega}{\nabla u\cdot\nabla vdx}$, $f(u)=\sinh (u)=\frac{e^u-e^{-u}}{2}$, and $H_g^1(\Omega)=\{u\in H^1(\Omega):\,u=g \text{ on } \partial \Omega\}$.

Note that there is no polynomial growth condition on the nonlinearity $f$ and so $f(u)$ is not supposed to be in $L^2(\Omega),\,\forall u\in H_g^1(\Omega)$. In $d=3$, there are functions $u\in H^1(\Omega)$ s.t $e^u\notin L^1(\Omega)$ (for instance $u=\ln\left(\frac{1}{r^\alpha}\right)\in H_0^1(B_1),\,\alpha\ge 3$ over the unit ball $B_1$).

Question: Is it true that equation $(*)$ is satisfied for all $v\in H_0^1(\Omega)$ ? (If there is an a priori estimate which gives $u\in L^\infty(\Omega)$ then $(∗)$ is obviously satisfied for all $v\in H_0^1(\Omega)$)

If it would help, we may assume that $f(u)\in L^1(\Omega)$.

If I have a positive answer to the question, this means that equation $(*)$ has a unique solution: suppose $u_1,u_2$ are solutions to $(*)$, then $a(u_1-u_2,v)+(f(u_1)-f(u_2),v)=0,\,\forall v\in H_0^1(\Omega)$ and so we can test with $u_1-u_2\in H_0^1(\Omega)$ and use the monotonicity property $(f(u_1)-f(u_2),u_1-u_2)\ge 0$ to conclude that $u_1=u_2$.

My try: From equation $(*)$ we see that $\left|\int\limits_{\Omega}{f(u)vdx}\right|\leq \|u\|_1\|v\|_1,\,\forall v\in H_0^1(\Omega)\cap L^\infty(\Omega)$ and therefore $f(u)$ defines a bounded linear functional over the dense subspace $H_0^1(\Omega)\cap L^\infty(\Omega)$ by the formula $\langle F,v\rangle=\int\limits_{\Omega}{f(u)vdx}$ and so it is uniquely extendable over the whole $H_0^1(\Omega)$ by continuity to the functional $\bar F\in H^{-1}(\Omega)$. However, the extension is not necessarily reprezentable by the same formula. Now, let $v\in H_0^1(\Omega)$ is arbitrary and $\{v_n\}\subset H_0^1(\Omega)\cap L^\infty(\Omega)$ s.t $$\begin{array}{|l} &v_n(x)\to v(x),\,a.e\\ & \|v_n-v\|_1\to 0 \end{array}$$ Then, $\int\limits_{\Omega}{f(u)v_ndx}=-a(u,v_n),\,\forall n$ and $a(u,v_n)\to a(u,v)\Rightarrow \int\limits_{\Omega}{f(u)v_ndx}\to -a(u,v)=:A$. Now, I want to conclude that $A=\int\limits_{\Omega}{f(u)vdx}$. We also have $f(u(x))v_n(x)\to f(u(x))v(x),\,a.e$ in $\Omega$ and $\int\limits_{\Omega}{f(u)v_ndx}=\langle F,v_n\rangle\to \langle \bar F,v\rangle$. But from here I still cannot show that $\int\limits_{\Omega}{f(u)v_ndx}\to \int\limits_{\Omega}{f(u)vdx}$.

I cannot use Lebesgue DCT, because I do not have a dominating function for $|f(u(x))v_n(x)|$. I thought also about the generalized Lebesgue DCT and maybe Vitali convergence theorem, but couldn't do it.

If we can use some type of regularity theory or maximum principle (which I do not know for this equation) and show that $u\in L^\infty(\Omega)$ or just that $f(u)\in L^{6/5}(\Omega)$, then $$\left|\int\limits_{\Omega}{f(u)(v_n-v)dx}\right|\leq \|f(u)\|_{L^{6/5}(\Omega)}\|v_n-v\|_{L^6(\Omega)}\leq C\|f(u)\|_{L^{6/5}(\Omega)}\|v_n-v\|_1\to 0$$ and I would be done.


You can show your regulary if $g \in W^{1,p}(\Omega)$, $p > d \ge 2$, by using a trick by Stampacchia.

First, we note $$a(u - g,v) + \int_\Omega f(u) v \, \mathrm{d} x = a(-g,v).$$

Now, let $K > 0$ and set $$(u - g)_K = \begin{cases} u - g & \text{if } |u - g| \le K, \\ \operatorname{sign}(u-g) \, K & \text{else}.\end{cases}$$ Then, $(u-g)_K \in H_0^1(\Omega) \cap L^\infty(\Omega)$.

Now, we choose $v = (u-g)_K$ and use $$a(u-g, (u-g)_K) = a((u-g)_K,(u-g)_K)$$ and $$\int_\Omega f(u) \, (u-g)_K \, \mathrm{d}x = \int_\Omega (f(u) - f(g)) \, (u-g)_K \, \mathrm{d}x + \int_\Omega f(g) \, (u-g)_K \, \mathrm{d}x \\\ge \int_\Omega f(g) \, (u-g)_K \, \mathrm{d}x$$ by monotonicity of $f$.

This shows $$ | (u-g)_K |_{H_0^1}^2 \le -\int_\Omega \nabla g \nabla (u-g)_K \, \mathrm{d}x - \int_\Omega f(g) \, (u - g)_K \, \mathrm{d}x$$ for all $K > 0$ and $\nabla g \in L^p(\Omega)$, $f(g) \in L^\infty(\Omega)$.

This estimate is enough to conclude $u - g \in L^\infty(\Omega)$. The detailed arguments can be found in many books, e.g., "An introduction to variational inequalities and their applications" by Kinderlehrer and Stampacchia, proof of Theorem B.2.

It is a remarkable feature of this trick that only the monotonicity of $f$ is used.

  • $\begingroup$ By the way, I managed to prove it by cutting off the test function in Theorem B.2. In this way it got quite complicated, but finally it worked. I couldn't prove it with the simpler cut-off test function that you suggested in your answer. I would like to ask you ( only in case you have done it before with the test function you suggested, otherwise do not waste time) how it is done. Thanks. $\endgroup$ – Svetoslav Jun 3 '16 at 17:14
  • $\begingroup$ At which part of the proof do you struggle? $\endgroup$ – gerw Jun 3 '16 at 18:07
  • $\begingroup$ Let $B(k):=\{x\in\Omega: |u-g|\ge k\}$ and $A(k):=\{x\in\Omega: |u-g|<k\}$. Then the RHS is estimated by $C(|\Omega|^{1/2}+|A(k)|^{1/3})\|\nabla (u-g)_k\|_{L^2(\Omega)}\quad (1)$ if we use the estimate $\int_\Omega f(u) \, (u-g)_K \, \mathrm{d}x \ge \int_\Omega f(g) \, (u-g)_K \, \mathrm{d}x$ that you wrote above. Or we can even improve this estimate if we take $k\ge \|g\|_{L^\infty(\Omega)}$ to estimate the RHS by $C(|A(k)|^{1/2}+|A(k)|^{1/3})\|\nabla (u-g)_k\|_{L^2(\Omega)}\quad (2)$. Now, we get $\|\nabla (u-g)_k\|_{L^2(\Omega)}\leq (1)$ or $\leq (2)$ $\endgroup$ – Svetoslav Jun 4 '16 at 21:44
  • $\begingroup$ Now, the LHS is estimated from below like: $\|\nabla (u-g)_k\|_{L^2(\Omega)}\ge C\|(u-g)_k\|_{H^1(\Omega)}\ge C\|(u-g)_k\|_{L^6(\Omega)}=\left(\int\limits_{\Omega}{|(u-g)_k|^6dx}\right)^{1/6}=\left(\int\limits_{A(k)}{(u-g)^6dx} + \int\limits_{B(k)}{k^6dx}\right)^{1/6}$. If $h>k$ we have $\ge \left(\int\limits_{A(h)\setminus A(k)\cup B(h)}{k^6}\right)^{1/6}=k(|A(h)|-|A(k)|+|B(h)|)^{1/6}\ge $ here we can continue in several ways, like $\ge (h-k)(|A(h)|-|A(k)|+|B(h)|)^{1/6},\,k<h<2k,\quad (*)$ or just leave it $\ge k|B(k)|^{1/6}\quad (**)$. $\endgroup$ – Svetoslav Jun 4 '16 at 22:02
  • $\begingroup$ On the other hand, if $h<k$ we can estimate the LHS from below like: $\|\nabla (u-g)_k\|_{L^2(\Omega)}\ge C\|(u-g)_k\|_{H^1(\Omega)}\ge C\|(u-g)_k\|_{L^6(\Omega)}=\left(\int\limits_{\Omega}{|(u-g)_k|^6dx}\right)^{1/6‌​}=\left(\int\limits_{A(k)}{(u-g)^6dx} + \int\limits_{B(k)}{k^6dx}\right)^{1/6}\ge \left(\int\limits_{A(k)\setminus A(h)}{(u-g)^6dx}+\int\limits_{B(k)}{k^6dx}\right)^{1/6}\ge h|B(h)|^{1/6}\quad (***)$. Or if in addition $h<k<2h$ we can get $\ge (k-h)|B(h)|^{1/6} (****)$. $\endgroup$ – Svetoslav Jun 4 '16 at 22:08

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.